Prenatal Substance Use Disorders and Dental Caries in Children. (April 2020) - Auger, N.; Low, N.; Lee, G.; Ayoub, A.; Nicolau, B.
Substance use is common in women of reproductive age, but limited data exist on the dental health of their children, including risk of caries. We conducted a longitudinal cohort study of 790, 758 infants born between 2006 and 2016 in Quebec, Canada. We identified women with substance use disorders before or during pregnancy. The main outcome measure was hospitalization for dental caries in offspring up to 12 y after birth. We estimated hazard ratios (HRs) with 95% confidence intervals (CIs) for the association of maternal substance use with pediatric dental caries, adjusted for potential confounders. Children exposed to maternal substance use had a higher incidence of hospitalization for dental caries than unexposed children (105.2 vs. 27.0 per 10, 000 person-years). Maternal substance use was associated with 1.96 times the risk of childhood dental caries (95% CI, 1.80–2.14), including a greater risk of caries of enamel, dentin, or cementum (HR, 2.00; 95% CI, 1.82–2.19) and dental pulp (HR, 2.36; 95% CI, 2.07–2.70), relative to no substance use. Associations were elevated for alcohol (HR, 2.31; 95% CI, 2.03–2.64) but were also present for cocaine, cannabis, opioids, and other substances. Substance use during pregnancy was more strongly associated with dental caries hospitalization than prepregnancy substance use. Associations were stronger in early childhood. Maternal substance use is associated with the future risk of dental caries hospitalization in children. Targeting substance use early in the lives of women may contribute to dental caries prevention in offspring.